Interactive Methods of Teaching English as a Second Language (ESL) in the Academic Classes (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
The purpose of the study was to study the impact of interactive methods on learning foreign languages .Though games and language have been treated as different psychological faculties, scientists has proved that interactive activities can be one of the efficient ways to improve students' language skills .In this article several interactive methods on improving students' language skills are studied. It is stated that interactive methods can be effective means in improving students' grammar, writing, speaking, reading and listening.